The functional requirements for trusted electronic records management systems / Nurussobah Hussin, Rusnah Johare and Adnan Jamaludin - Johare, Rusnah; Jamaludin, Adnan; Hussin, Nurussobah (Faculty of Information Management, 2013)
The purpose of this paper is to examine the characteristics and nature of functional requirements for electronic records management systems (ERMS). It attempts to highlight several electronic records management systems functional requirement models developed aiming at facilitating an efficient and effective electronic records management.The study employed literature reviews to gather information on functional requirements of the leading advocates on electronic records management. It provides a critical analysis of several electronic records management systems functional requirement models such as the Trust Model; Business-Driven Recordkeeping Model; and the ICA Model of High level Functional Requirements for ERMS. The findings illustrate that ERMS functional requirements are important to protect the reliability, accuracy, authenticity and the trustworthiness of electronic records as evidence, thus establishing the trusted electronic records management systems. The insights in this paper will be useful to stakeholders and key players in electronic records management such as archivists, records managers, administrators and IT personnel.